Design and Synthesis of Two-Photon Responsive Chromophores for Near-Infrared Light-Induced Uncaging Reactions - Abe, Manabu; Chitose, Youhei; Jakkampudi, Satish; Thuy, Pham Thi Thu; Lin, Qianghua; Van, Bui Thi; Yamada, Ayato; Oyama, Ryoko; Sasaki, Miyu; Katan, Claudine (Synthesis, 2017)
Near-infrared two-photon (TP)-induced photorelease (uncaging) of bioactive molecules such as drugs has attracted considerable attention because of its ability to elucidate mechanistic aspects of biological processes. This short review summarizes recent developments in the design and synthesis of TP-responsive chromophores.1 Introduction2 Molecular Design of TP-Responsive Organic Chromophores for ‘Caging & Uncaging’2.1 π-Conjugation2.2 A Dipolar System2.3 A Quadrupolar System2.4 An Octupolar System3 Recent Developments of TP Uncaging Reactions3.1 4-Methoxy-7-nitroindolinyl Caged Auxins3.2 Uncaging of GABA and Tryptophan Using TP-Induced Electron-Transfer Reactions3.3 Effect of Position Isomery in Aminoquinoline-Derived Photolabile Protecting Groups (PPGs)3.4 Cooperative Dyads for TP Uncaging3.5 Caged Calcium with a Bis-styrylthiophene Backbone3.6 Cloaked Caged Compounds3.7 Three-Dimensional Control of DNA Hybridization by Orthogonal Two-Color TP Uncaging3.8 TP-Induced Release of Diethyl Phosphate (DEP) and ATP4 Our Contribution to TP Uncaging Reactions5 Summary
Keywords: caging reactions; uncaging reactions; photolabile protecting groups; two-photon absorption; time-dependent density functional theory